APPLICATION OF PROCEDURAL CONTENT GENERATION SYSTEM IN FORMING DUNGEON LEVEL IN DUNGEON DIVER GAME - Eka Wahyu Hidayat; Euis Nur Fitriani Dewi; Insan Saleh Ramadhan (Jurnal Teknik Informatika (Jutif), 2024)
Developers face numerous challenges in game development, one of which is the lack of games replayability due to the limited variety of levels created. The absence of level variety can lead to player boredom. The Procedural Content Generation (PCG) method provides an effective solution to address this challenge. PCG is applied with a focus on the Cellular Automata method by implementing the Von Neumann Neighborhood rule. The objective of this paper is to apply the Procedural Content Generation System method to create levels in game development. The game development process utilizes Luther's MDLC method. Testing is conducted using tiles of 32x32 units and 64x64 units, with three different test parameters: a fill percentage of 25%, 45%, and 65%. Each fill percentage is tested with three different smooth amount parameters of 2, 4, and 6, with a randomly selected seed. Performance testing results indicate that creating dungeon levels with 32x32 and 64x64 tiles yields short and relatively similar times, around 0.08 to 0.3 seconds. Functional testing reveals that a 25% fill percentage results in nearly empty rooms with no footholds, a 45% fill percentage produces levels with space and footholds, while a 65% fill percentage generates small unconnected rooms. Based on these percentages, a 45% fill percentage is considered the most appropriate for creating dungeon levels because it provides suitable space and footholds for players. Implementing PCG in game level creation not only saves time compared to manual level creation but also offers more efficient variations in dungeon shapes and difficulty levels.